General characteristics of the national system of scientific and technical information in the Republic of Moldova - V. Dogotar; A. Yurutkina (Informaciâ i Innovacii)
The article considers the main characteristics of the national system of scientific and technical information in the Republic of Moldova. In the context of determining the possible development prospects of this system, such areas are studied as: structure and special centers for managing scientific and technical information, the main directions of state policy, financing of projects in 2019, as well as scientific journals.